Revolution now. Public health beyond capitalism - Chiara Francesca Bodini (Social Medicine Publication Group, 2021)
Critical thinking in public health is well and alive, ad least by looking at the numbers and content of the last conference of the International Association of Health Policy in Europe (IAHPE). The scientific organisation gathers a number of well known scientists and academics sharing a starting point that can be captured in the slogan "capitalism is bad for our health". Founded in 1977 as the International Association of Health Policy (IAHP), the European branch - 'sister' to the Latin American Association of Social Medicine (ALAMES) - holds international conferences every two or three years. The last one - number 18 in the history of the association - took place from the 21st to the 24th of September in Thessaloniki, Greece, organised by the Aristotle University of Thessaloniki in collaboration with the Queen Mary University of London. Over 30 speakers from all over the world presented critical analysis on health policies and outcomes "in the era of capitalist crisis and restructuring" - as explained by the title of the conference - during seven round table discussions and five key note lectures; in addition, numerous researchers animated parallel sessions presenting posters and papers of high scientific and political value. It's impossible to summarise the richness in analysis and perspectives brought by all the contributors, but I'll try to highlight some aspects worth being widely shared.